Friedländer annulation: scope and limitations of metal salt Lewis acid catalysts in selectivity control for the synthesis of functionalised quinolines. (20th October 2015) - Tanwar, Babita; Kumar, Dinesh; Kumar, Asim; Ansari, Md. Imam; Qadri, Mohammad Mohsin; Vaja, Maulikkumar D.; Singh, Madhulika; Chakraborti, Asit K.
Abstract : In(OTf)3 is the most effective catalyst among metal halides, tetrafluoroborates, perchlorates, and triflates for Friedländer quinoline synthesis in 75–92% yields. Abstract : The scope and limitations of metal salt Lewis acid catalysts were examined for the selectivity control for the formation of Friedländer and non-Friedländer products during the reaction involving 2-aminobenzophenone and ethyl acetoacetate. Among a pool of metal halides, tetrafluoroborates, perchlorates, and triflates used as catalysts, In(OTf)3 emerged as the most effective catalyst for the selective/exclusive formation of the Friedländer product. The generality of the In(OTf)3 -catalysed Friedländer reaction was demonstrated by the reaction of differently substituted 2-aminoarylketones with various carbonyl compounds containing an active methylene group ( e.g., β-ketoesters, cyclic/acyclic β-diketones, cyclic/acylic ketones, and aryl/heteroaryl methyl ketones) under solvent-free conditions affording the desired quinolines in 75–92% yields.